Developing person-centred leadership practices: Health and social care leaders’ experiences following an educational programme - Charlotte Klinga; Qarin Lood; Eric Carlström; Emmelie Barenfeld (PLoS ONE, 2026)
Objective Educational programmes aimed at nurturing person-centred leadership are requested to advance the implementation of person-centred care, however there is a scarcity of evaluations. This study aimed to explore health and social care leaders’ experiences of changes in leadership practices following participation in an educational programme on person-centred leadership. Design A qualitative exploratory research approach, with individual interviews analysed using conventional content analysis, including an interpretative step linking categories to an overarching theme using three leadership concepts. Setting Health and social care services in Sweden. Participants Thirteen leaders were purposefully selected according to sampling criteria. Results The programme did, according to the participants, contribute to the development of person-centred leadership practices by enhancing self-leadership, team leadership, and workforce development aligned with person-centred principles. Three categories unfolded this process: Live as you learn , Strive for equal relations , and Enable co-creation , which were further detailed into nine sub-categories. The results were influenced by various preconditions for continuous learning. Conclusion The findings emphasise the necessity of establishing preconditions promoting person-centred leadership (e.g., continuous support from other leaders, time to coach teams and establishing empowering working methods) for continuous development during and after the educational programme. When these preconditions were met, the programme was experienced to effectively influence self-leadership, enhance team leadership, and promote workforce development in line with person-centred principles. Implications It is crucial to integrate practical assignments into workplace settings, address daily challenges, and involve leaders, employees, patients, and their relatives early on. This approach supports the continuous development of leadership practices and ensures the sustainable transformation of health and social care practices towards person-centred care. The programme’s theoretical foundation was considered applicable in supporting leadership development, but more research is needed to evaluate the impact and effect of person-centred leadership programmes over time from leaders’, employees’, and patients’ perspectives.